Pengaruh Harga dan Online Customer Review Terhadap Keputusan Pembelian Case Handphone Pada Marketplace Shopee : Studi kasus Mahasiswa Manajemen Stambuk 2020 Universitas Pembangunan Panca Budi Medan - Firdiya Amiyananda; Ramadhan Harahap; Annisa Sanny (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research aims to assess the Influence of Price and Online Customer Reviews on Purchasing Decisions for Handphones on the Shopee Platform, with a focus on Management students from Panca Budi Development University in Medan, batch 2020. The method employed is quantitative, involving 78 respondents who are consumers that have purchased phone cases online through Shopee. Data was collected through questionnaire distribution, and analysis was conducted using SPSS software version 22. The study also encompasses multiple linear regression, instrument testing, classical assumption testing, and hypothesis testing to bolster findings. The results indicate that both Price and Online Customer Reviews have significant partial and simultaneous impacts on Purchasing Decisions for Handphones on Shopee.